Vida e sentidos na perspectiva de Viktor Frankl: um estudo sobre o sentido da vida e do trabalho na atualidade - Dall Bello, Camila (2019)
The countless transformations that the world, society and the subject face are directly reflected in the meaning attributed to people's lives, existence, the way they relate, work and live in society. One notices a “discomfort” in society, which also affects the work. The number of cases of mental illness is increasing, the need for medicalization, leading to the removal of social and working life, and even suicide. There are still few studies in the literature that relate the meaning of life and work in an interconnected way. This dissertation aims to evaluate, from the works of psychologist and neuropsychiatrist Viktor Emil Frankl, how the subject perceives the meaning of life and work today and the relationship established between them. Frankl, in his studies, envisions a “mass neurosis” in society, verifying a strong sense of existential emptiness and meaninglessness. The applied research, at a descriptive level and through a qualitative approach, had the participation of 18 subjects, of both sexes, aged between 20 and 78 years old, who have or have had contact with the world of work, residing in the microregion from Erechim (RS), Brazil. A convenience sampling was adopted and a sociodemographic questionnaire and an interview based on a semi-structured question script were applied. The transcribed speeches were treated by Bardin content analysis. The resulting production of this study, entitled "The relationship between the meaning of life and work from the perspective of Viktor Emil Frankl" sought to understand how the meaning of life and work are apprehended for different subjects today. From the analysis of the participants' reports it was possible to observe different positions in the perspective of being and having in and through work, mental health producer and determinant in the subject's identity. Work thus constitutes itself as an anchor to all other forms attributed as meaning to life.